Novel GLA Deletion in a Cypriot Female Presenting with Cornea Verticillata. (30th March 2016) - Georgiou, Theodoros; Mavrikiou, Gavriella; Alexandrou, Angelos; Spanou-Aristidou, Elena; Savva, Isavella; Christodoulides, Theodoros; Krasia, Maria; Christophidou-Anastasiadou, Violetta; Sismani, Carolina; Drousiotou, Anthi; Tanteles, George A.
Abstract : Fabry disease is an X-linked lysosomal storage disorder resulting from a deficiency of the hydrolytic enzyme α -galactosidase A ( α -Gal-A). It is characterized by progressive lysosomal accumulation of globotriaosylceramide (Gb3) and multisystem pathology, affecting the skin, nervous and cerebrovascular systems, kidneys, and heart. Heterozygous females typically exhibit milder symptoms and a later age of onset than males. Rarely, they may be relatively asymptomatic throughout a normal life span or may have symptoms as severe as those observed in males with the classic phenotype. We report on a 17-year-old female in whom cornea verticillata was found during a routine ophthalmological examination but with no other clinical symptoms. Leucocyte α -galactosidase activity was within the overlap range between Fabry heterozygotes and normal controls. Sanger sequencing of the GLA gene failed to reveal any pathogenic variants. Multiplex Ligation-dependent Probe Amplification (MLPA) analysis revealed a deletion of exon 7. Using a long-range PCR walking approach, we managed to identify the deletion breakpoints. The deletion spans 1182 bp, with its 5′ end located within exon 6 of the GLA gene and its 3′ end located 612 bp downstream of exon 7. This finding represents a novel deletion identified in the first reported Cypriot female carrier of Fabry disease.